Togo : 2016 Article IV Consultation and Request for a Three-Year Arrangement Under the Extended Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Togo. (IMF Staff Country Reports; Country Report ;, 2017)
This 2016 Article IV Consultation highlights the healthy rate of expansion in the economy of Togo in recent years. Growth was 5.2 percent in 2014-16. Inflation was well contained, explained by the lower food, energy, and transportation prices. Togo's poverty rate declined from 61.7 percent in 2006 to 55.1 percent in 2015, though it remains geographically concentrated. Economic growth is expected to increase gradually in the medium term as the fiscal stance is put on a sustainable path. Growth is expected to pick up from 5 percent in 2016 to 5.6 by 2021, with the economy reaping the benefits of an improved transportation network and productivity gains in the agricultural sector.